IDENTIFIKASI WASTE DI RUANG RAWAT JALAN DAN RAWAT INAP RUMAH SAKIT ISLAM SURABAYA - Puryanti Puryanti (Medical Technology and Public Health Journal, 2018)
Hospitals as healthcare providers are demanded more competitive in the era of national health insurance. Therefore the hospital faces the challenges of improving the quality of health services by using available resources. The study aims to to identify waste in outpatient and inpatient rooms of Surabaya Islamic Hospital. The descriptive study involved 90 patients from outpatient and inpatient rooms. The study found waste by defect category, waiting time, non utilize talent, transportation, inventory, motion, and extra processing based on business process analysis. Category of waste over production not found. The causes of the occurrence of waste most comes from the man, material, and method factors. Program recommendations include scheduling patient-based arrival of service group, visite scheduling and polyclinic service and temporary payment method change, for inpatient program program consisting of 5R program implementation, rearranging standard operating procedure of patient's diet information, improvement of prescribing system for patient and standard operating procedure rearrangement return of insurance patients.